ENHANCING THE EXCELLENCE OF ISLAMIC BOARDING SCHOOLS THROUGH TRANSFORMATIVE LEADERSHIP - Khotimah, Husnul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze how transformative leadership can increase the excellence of Islamic boarding school organizations. The Nurul Jadid Paiton Probolinggo Islamic Boarding School has implemented transformative leadership to increase organizational excellence. This research uses a qualitative case study type approach, data collection techniques in the form of field observations, interviews and document analysis. The researcher's data analysis technique consists of three stages: data reduction, data presentation, conclusions and verification. The research results show that transformative leadership increases the excellence of Islamic boarding school organizations through transformative leadership steps such as: Creating a clear vision, innovation and creativity, motivating the team, having a role model from a leader, flexibility and adaptability, building a learning culture within the organization. This is very influential on the discipline of female students and the effectiveness of teaching and learning activities at Madrasah Diniyah Takmiliyah Fathimatuzzahro